Fluorescence-guided tumor resection with a cathepsin B-activatable, EGFR-targeted probe and a dual-mode surgical exoscope - Sung, Yejin; Choi, Youngjin; Park, Sang Mi; Choi, Nakwon; Lee, Sangmin; Suh, Seung Beum; Kim, Chansoo; Hur, Wooyoung; Cho, Seung-Woo; Lee, Deukhee; Ryu, Ju Hee (Elsevier BV, 2025)
Fluorescence-guided surgery enhances surgical precision by enabling real-time tumor visualization. Here, we developed a cathepsin B-activatable imaging probe conjugated to the EGFR-targeting antibody cetuximab (Cetux-CB probe) for fluorescence-guided resection of triple-negative breast cancer (TNBC). The probe consists of a cathepsin B-sensitive peptide linker, a near-infrared fluorophore (FlammaTM Fluors 749), and a quencher (qFlamma Black01), enabling enzymatic activation following tumor-specific accumulation. The Cetux-CB probe exhibited robust cathepsin B-dependent fluorescence activation in EGFR-overexpressing TNBC cells and xenograft tumors, with high tumor accumulation and minimal background in normal tissues. Following systemic administration, the probe demonstrated prolonged and confined fluorescence in vivo, outperforming both non-targeted and always-on fluorescent controls. When combined with a dual-mode surgical exoscope, the probe allowed precise intraoperative tumor localization and guided accurate incision and dissection, confirmed by the absence of residual signal. This study demonstrates the clinical potential of combining dual-responsive imaging probes with compatible imaging systems to improve surgical outcomes in TNBC and other EGFR-positive cancers.